[LB.01.26] RECLASSIFICATION OF ELEVATED BLOOD PRESSURE SUBTYPES AND STAGES BASED ON REPEATED MEASUREMENTS AMONG CHINESE SCHOOLCHILDREN. (September 2017) - Dong, H.; Yan, Y.; Fan, H.; Liu, J.; Cheng, H.; Zhao, X.; Huang, G.; Mi, J.
Abstract : Objective: Due to the variability of childhood blood pressure(BP), several guidelines recommend that elevated BP (EBP) in children and adolescents should be determined based on at least three separate visits. However, data regarding the subtypes and their fluctuations during this process is limited. In this study, we sought to assess the proportion and change of EBP classifications over repeated measurements. Design and method: Oscillometric BP measurements were obtained from a general population, comprising 44, 328 children and adolescents aged 6–17 years old from six urban cities in mainland China. Those with EBP (at least 95th centile) were screened a second or third time at a month interval. In addition, EBP at each screening was further classified according to BP stages (stage 1 and stage 2) and BP subtypes (isolated systolic EBP, isolated diastolic EBP, and systolic-diastolic EBP). Results: After 3 separate consecutive visits, isolated systolic EBP and stage 1 EBP sustained to be the major type of EBP subtypes and stages. Meanwhile, there were increases in the relative proportion of isolated systolic EBP, systolic-diastolic EBP and stage 2 EBP, and concurrent decreases in isolated diastolic EBP and stage1 EBP. In the last two visits, approximately 50% of subjects diagnosed with EBP at a former visit had their BP normalized, which was mostly found among those with isolated diastolic EBP and those with stage 1 EBP. Apart from that, subjects with isolated diastolic EBP and those with stage 2 EBP exhibited higher proportion of reclassification within EBP subtypes and stages; they were more likely to shift to isolated systolic EBP and stage 1 EBP, respectively. Compared with normotensives, subjects that changed their BP classification were younger, with higher proportion of boys and higher levels of heart rate, body mass index, and triglyceride. Conclusions: After 3 repeated measurements, less than half of the population diagnosed with EBP at the first visit maintained their classification, which was even less in the group of isolated diastolic EBP. Repeated measurements in obese children (<12 years) may lead to more accurate classification of BP types and stages. Figure. No caption available.